2023
DOI: 10.1038/s41598-023-42044-x
|View full text |Cite
|
Sign up to set email alerts
|

CCIVR2 facilitates comprehensive identification of both overlapping and non-overlapping antisense transcripts within specified regions

Maya Suzuki,
Satoshi Sakai,
Kosuke Ota
et al.

Abstract: Pairs of sense and antisense transcriptions that are adjacent at their 5′ and 3′ regions are called divergent and convergent transcription, respectively. However, the structural properties of divergent/convergent transcription in different species or RNA biotypes are poorly characterized. Here, we developed CCIVR2, a program that facilitates identification of both overlapping and non-overlapping antisense transcripts produced from divergent/convergent transcription whose transcription start sites (TSS) or tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…We found that the corresponding annotations for these overlapping transcript pairs are oriented preferentially in a configuration with their 5′ ends exposed for degradation by XRN1 rather than the configuration where the 5′ ends are protected from XRN1 degradation ( Figure S5F and Table S5 ), as determined by the comprehensive cis -natural anti-sense transcripts identifier via RNA-sequencing data (CCIVR2) computational tool. 35 The exposed 5′ ends of these annotated overlapping transcripts also contain at least four “overhanging” base pairs in 98.0% of 150 transcripts ( Figure S5G and Table S5 ), consistent with findings from RNA:DNA hybrid substrates that are susceptible to XRN1 degradation. 25 These data suggest that XRN1 deletion in HCC366 cells causes accumulation of complementary sense/anti-sense transcripts that are normally degraded by XRN1.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…We found that the corresponding annotations for these overlapping transcript pairs are oriented preferentially in a configuration with their 5′ ends exposed for degradation by XRN1 rather than the configuration where the 5′ ends are protected from XRN1 degradation ( Figure S5F and Table S5 ), as determined by the comprehensive cis -natural anti-sense transcripts identifier via RNA-sequencing data (CCIVR2) computational tool. 35 The exposed 5′ ends of these annotated overlapping transcripts also contain at least four “overhanging” base pairs in 98.0% of 150 transcripts ( Figure S5G and Table S5 ), consistent with findings from RNA:DNA hybrid substrates that are susceptible to XRN1 degradation. 25 These data suggest that XRN1 deletion in HCC366 cells causes accumulation of complementary sense/anti-sense transcripts that are normally degraded by XRN1.…”
Section: Resultssupporting
confidence: 77%
“…In addition, although it is tempting to consider whether inhibition of XRN1 may be an effective therapeutic strategy in human cancer, Xrn1 deletion in mice results in embryonic lethality, 35 suggesting that XRN1 inhibition may cause substantial toxicity. Thus, XRN1 would need to be targeted specifically or at least preferentially in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative strength of competing sense and antisense promoters could therefore program the frequency at which specific differentiation events occur. A recent comprehensive evaluation of antisense transcription across multiple species revealed a similar pattern of convergent and divergent antisense TSS near the start site of genes in xenopus, chicken, mouse, and human, with a clustering of divergent antisense within 200 bp and convergent antisense within 2 kb [24].…”
Section: Gata Switches and The Role Of Noncoding Rna In Differentiationmentioning
confidence: 96%